Imposto sobre grandes fortunas: análise a partir do princípio da capacidade contributiva em prol da justiça distributiva - Dantas, Soraya Braga de Sousa (2019)
This dissertation is about the viability of the implementation of the Tax on Large Fortunes, which already has provision in the Magna Carta, but is not regulated, which leads to its possible effects in the Brazilian tax sphere. The basis of this investigation was to think of this tax from the point of view of the principle of contributory capacity, considered a corollary of the principle of Equality. In the midst of the economic crisis faced by Brazil, exploring this theme became relevant mainly because of its controversial character. In this context, the objective was to approach the institution of this tax by considering the possibility that each individual has to contribute with public revenue in order to allow the State to assure its people a better quality of life, reduce social and economic inequalities, and , in this way, guarantee the existential minimum. Thus, at first, an attempt was made to understand the principle of contributory capacity, its emergence, characteristics and scope. Next, we examined the Tax on the Great Fortunes, its history, concept, as well as the viability of its implementation when comparing the legal opinions on the subject and then arriving at a final consideration that substantiates the tax justice. In addition to this, the bills that deal with the tax in question were presented and analyzed. Therefore, the study proposed to understand the importance of distributive justice because it is linked to the dignity of the human person and stressed the importance of the realization of the social rights stipulated by the constitution. It was an exploratory research, using the method of deductive approach in addition to the methods of historical and comparative procedure, from a documentary and bibliographical review.